12-2(7+2t)=2(t-1)

Simple and best practice solution for 12-2(7+2t)=2(t-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12-2(7+2t)=2(t-1) equation:


Simplifying
12 + -2(7 + 2t) = 2(t + -1)
12 + (7 * -2 + 2t * -2) = 2(t + -1)
12 + (-14 + -4t) = 2(t + -1)

Combine like terms: 12 + -14 = -2
-2 + -4t = 2(t + -1)

Reorder the terms:
-2 + -4t = 2(-1 + t)
-2 + -4t = (-1 * 2 + t * 2)
-2 + -4t = (-2 + 2t)

Add '2' to each side of the equation.
-2 + 2 + -4t = -2 + 2 + 2t

Combine like terms: -2 + 2 = 0
0 + -4t = -2 + 2 + 2t
-4t = -2 + 2 + 2t

Combine like terms: -2 + 2 = 0
-4t = 0 + 2t
-4t = 2t

Solving
-4t = 2t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-2t' to each side of the equation.
-4t + -2t = 2t + -2t

Combine like terms: -4t + -2t = -6t
-6t = 2t + -2t

Combine like terms: 2t + -2t = 0
-6t = 0

Divide each side by '-6'.
t = 0

Simplifying
t = 0

See similar equations:

| 5x^2=42x+27 | | 3y+x=-16 | | 3y+x=-16 | | (4x-5)/(3x+7) | | 4(4-8y)-y=3y+7 | | 2/3c+4=15 | | f(x)=-3 | | 8=3c-7 | | 3x+1/4=4x+3/4 | | 2x^2-27x+168=0 | | 3y+14=5y | | 10x+9=3(3x+2) | | x^4-10x^2+40=0 | | U-3/u-2=4/u+4 | | 59x=-2-1+3 | | v+5/6v-1/6=(3/8v+1/4) | | -6(n+2)+13=-3n-8 | | 5g+11=-3 | | -2x+10-4=6 | | 2x^3+27=0 | | 2/3x-1/4+4/3x+3/4=6 | | 2(5c-1)-5=(8c+5) | | 4-1/2d=10 | | 3x+2x=5+3x | | N+2n=30 | | 6x+4x=74 | | 4.0=8.4/X | | 6(a-6)=48 | | a^3x-9ax^3=0 | | (p-6)(p-7)=0 | | 3x+2x=5+3 | | 3(d-4)=15 |

Equations solver categories